2022
DOI: 10.3389/fnut.2022.872773
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up Study of Ovarian Cancer (OOPS): A Study Protocol

Abstract: The ovarian cancer (OC) follow-up study (OOPS) is an on-going hospital-based large prospective longitudinal cohort study aimed to explore the relationship between pre/post-diagnostic biological, clinical, environmental, and lifestyle factors with focus on the diet and OC prognosis (including drug resistance, relapse, and mortality). Patients recruited during the baseline survey were between 18 and 79 years old, with histologically confirmed OC diagnosis. Their follow-up and medical treatment were conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Dietary information was gathered via a validated 111-item food frequency questionnaire (FFQ), which was previously validated. 16,17 The reproducibility coefficients (Spearman correlation coefficients and intraclass correlation coefficients) for most food groups were above 0.5, and correlation coefficients (Spearman correlation coefficients) for most food groups between the FFQ and weighed diet records were between 0.3 and 0.7. In this study, participants were asked how often, on average, they had consumed various foods over the 12 months prior to OC diagnosis, with 7 predefined frequency categories ranging from almost never to 2 or more times per day.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Dietary information was gathered via a validated 111-item food frequency questionnaire (FFQ), which was previously validated. 16,17 The reproducibility coefficients (Spearman correlation coefficients and intraclass correlation coefficients) for most food groups were above 0.5, and correlation coefficients (Spearman correlation coefficients) for most food groups between the FFQ and weighed diet records were between 0.3 and 0.7. In this study, participants were asked how often, on average, they had consumed various foods over the 12 months prior to OC diagnosis, with 7 predefined frequency categories ranging from almost never to 2 or more times per day.…”
Section: Methodsmentioning
confidence: 94%
“…Study patients with OC were identified from the ovarian cancer follow-up study (OOPS), which was described previously. 16,17 Briefly, the OOPS is a prospective longitudinal cohort study of patients newly diagnosed with OC. The OOPS was approved by the Institutional Review Board of the Ethics Committee of Shengjing Hospital of China Medical University, Shenyang, China, and informed consent was obtained from all patients.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the design and method of OOPS has been provided previously. 12,30 As of December 2020, 853 patients newly diagnosed with OC, aged 18-79 years, were recruited. We excluded the following OC patients: (1) those who refused to participate in this study (n = 57) or did not return questionnaires (n = 52), (2) those who left 11 (10%) or more food items blank (n = 24), (3) those who reported with implausible caloric intakes (<500 or >3500 calories per day) 33 (n = 17), and (4) those who were smokers (n = 68); 635 OC patients were eligible for the present analysis (Fig.…”
Section: Study Populationmentioning
confidence: 99%
“…The Australian Ovarian Cancer Study (AOCS), involving 1270 women with invasive epithelial OC, suggested no association between total choline and betaine intake and OC survival. 29 However, based on the Ovarian Cancer Follow-Up Study (OOPS), 30 our colleagues found that total choline intake is inversely associated with OC survival, but no relationship between betaine intake and OC survival. 31 However, different forms of choline vary in absorption, metabolism and functions, 15 and water-soluble forms of choline enter the enterohepatic circulation through portal circulation, while lipid soluble forms are absorbed and transported through lymphatic circulation in the form of chylomicrons, 15 which suggests that the forms of choline should also be considered.…”
Section: Introductionmentioning
confidence: 99%